Nanometer ZSM-5 molecular sieve aggregate as well as preparation method and application thereof
By regulating the dissolution of silica source and crystal growth under hydrothermal conditions, nano ZSM-5 molecular sieve aggregates are prepared, which solves the problem of difficulty in collecting traditional microporous molecular sieves under nano size, and achieves efficient preparation and recycling, reduces production costs, and improves catalytic activity.
Patent Information
- Application Number
- CN202311398366.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-25
- Publication Date
- 2025-04-25
AI Technical Summary
Traditional microporous molecular sieves are difficult to collect by filtration when their grain size is less than 400nm, resulting in high production costs and limiting the production application of nanomolecular sieves.
By regulating the synthesis conditions, dissolving the silicon source, nucleating the crystals, and growing the crystals under hydrothermal conditions, nano ZSM-5 molecular sieve aggregates were prepared. The solid-phase silicon source and in-situ synthesis methods were used to control the primary crystal grain size of the molecular sieve to be nanoscale and recovered by filtration.
The efficient preparation and easy recycling of nano ZSM-5 molecular sieve aggregates is achieved, reducing production costs, and improving the catalytic activity and wear resistance of molecular sieves.
Smart Images

Figure CN119873856A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to the technical field of molecular sieve synthesis, and in particular, to a nano ZSM-5 molecular sieve aggregate and a preparation method and application thereof. Background Art
[0002] In order to alleviate the mass transfer limitation of traditional microporous molecular sieves, a large number of studies have been devoted to the preparation of nanomolecular sieves with smaller crystal sizes. However, when the crystal size of the molecular sieve is too small (less than 400nm), it is difficult to collect samples by filtration, and high-speed centrifugation and other means are often required to collect the product. This problem will significantly increase the production cost and limit the production and application of small-crystal molecular sieves.
[0003] A large number of studies are devoted to making molecular sieve products easier to recycle under the premise of maintaining the performance of nanomolecular sieves. At present, preparing nanomolecular sieves as micrometer-scale aggregates is an effective means to strengthen the diffusion advantage of nanomolecular sieves and take into account the recovery efficiency. Yu Han et al. used triblock copolymer F127 to assemble 100nm nanomolecular sieves into micrometer-scale aggregates during the synthesis process (Chem. Mater., 2009, 21, 2344); Tang Yi et al. used urea-formaldehyde polymer polymerization to induce the assembly of nanomolecular sieves to form microspheres (Chem. Mater. 2006, 18, 1861-1866). CN102872909A reports the use of mesoporous particles with positive charges on the surface to bond molecular sieve nanoparticles with negative charges on the surface, and the electrostatic interaction between molecular sieve nanoparticles and mesoporous particles is combined to obtain nanomolecular sieve aggregates. In the prior art, the formation of the above-mentioned nanomolecular sieve aggregates is all assembled by organic matter to synthesize the molecular sieve, and the organic materials need to be removed by post-processing. The method is relatively cumbersome, the raw material cost is high, and the post-processing step has high energy consumption.
[0004] Some studies have reported methods for assembling and molding molecular sieves without using organic materials. For example, CN1105906A reported a method for preparing a binder-free ZSM molecular sieve, which uses a mixture of a silicon oxide binder and ZSM molecular raw powder, and converts it into an integrated ZSM molecular sieve through hydrothermal treatment in a template aqueous solution or steam; however, the primary grain size of the molecular sieve product obtained by the above method is difficult to control to the nanometer level, and the method requires the molecular sieve raw powder to be obtained in advance, and it is still difficult to avoid the problem of recycling nanomaterials in the process of obtaining the nano molecular sieve raw powder. Summary of the invention
[0005] The purpose of the present disclosure is to provide a nano ZSM-5 molecular sieve aggregate and a preparation method and application thereof. The method can control the primary grain size of the molecular sieve product to be nanometer-level, and the obtained nano ZSM-5 molecular sieve aggregate is easy to filter and recover, thereby reducing industrial production costs.
[0006] In order to achieve the above object, the present disclosure provides a method for preparing nano ZSM-5 molecular sieve aggregates in a first aspect, the method comprising the following steps:
[0007] (1) mixing an organosilicon source, ethanol and water for a first mixing, and then adding a template for a second mixing to obtain a seed crystal mother solution; subjecting the seed crystal mother solution to a first crystallization reaction, and separating seed crystals from the obtained material;
[0008] (2) mixing an aluminum source, an alkali source and water for a third mixing, adding an inorganic silicon source for a fourth mixing, then adding the seed crystals described in step (1) for a fifth mixing to obtain a crystallization precursor solution;
[0009] (3) subjecting the crystallization precursor solution to a second crystallization reaction and a third crystallization reaction in sequence, wherein the temperature of the second crystallization reaction is higher than the temperature of the third crystallization reaction by more than 30° C.;
[0010] Wherein, in step (2), the inorganic silicon source is one or more of diatomaceous earth, white carbon black and solid silica gel, and the average particle size of the inorganic silicon source is 0.05-25 μm; the seed crystal is 2 The mass ratio of the inorganic silicon source is 1-10:1.
[0011] Optionally, in step (1), the first mixing conditions include: stirring at a temperature of 20-35° C. for 0.5-2 h; the second mixing conditions include: stirring at a temperature of 50-80° C. for 4-8 h;
[0012] In step (1), SiO 2 The molar ratio of the organosilicon source, the ethanol, the template and the water is 1:(3.2-4.8):(0.16-0.24):(48-72);
[0013] The conditions of the first crystallization reaction include: temperature of 110-130° C., time of 16-72 h, and the first crystallization is static crystallization;
[0014] The organic silicon source is orthosilicate, and the orthosilicate is selected from one or more of tetraethyl orthosilicate and methyl orthosilicate;
[0015] The template agent is a quaternary ammonium compound, and the quaternary ammonium compound is selected from one or more of tetrapropylammonium hydroxide, tetramethylammonium hydroxide and tetraethylammonium hydroxide.
[0016] Optionally, in step (2), the third mixing conditions include: stirring at a temperature of 20-35°C for 0.5-2h; the fourth mixing conditions include: stirring at a temperature of 50-80°C for 2-4h; the fifth mixing conditions include: stirring at a temperature of 50-80°C for 1-4h.
[0017] Optionally, in step (2), SiO 2 The inorganic silicon source is Al 2 O 3 The aluminum source is calculated as Na 2 The molar ratio of the alkali source in terms of SiO2 to the water is 1:(0.012-0.018):(0.12-0.18):(25-38); the seed crystal and the SiO2 2 The mass ratio of the inorganic silicon source is 3-10:1.
[0018] Optionally, in step (2), the aluminum source is an aluminum-containing compound selected from one or more of sodium aluminate, aluminum chloride, aluminum sulfate, aluminum isopropoxide and aluminum nitrate; the inorganic silicon source is SiO 2 A solid silicon source having a content higher than 90% by weight; the alkali source is selected from one or more of sodium hydroxide and potassium hydroxide.
[0019] Optionally, step (2) further comprises adding a structural aid during the fifth mixing; the structural aid is a water-soluble inorganic sodium salt selected from one or more of sodium bromide, sodium chloride, sodium nitrate and sodium carbonate; the structural aid is mixed with SiO 2 The molar ratio of the inorganic silicon source is 0.12-0.18:1, preferably 0.13-0.17:1.
[0020] Optionally, in step (3), the conditions of the second crystallization reaction include: temperature of 190-220°C, time of 0.5-3h, and the second crystallization reaction is dynamic crystallization; the conditions of the third crystallization reaction include: temperature of 150-180°C, time of 6-15h, and the third crystallization reaction is dynamic crystallization; the temperature of the second crystallization reaction is 30-50°C higher than the temperature of the third crystallization reaction.
[0021] Optionally, the method further comprises: filtering, washing, drying and roasting the product obtained in step (3) in sequence; the roasting conditions include: temperature of 500-600° C. and time of 4-8 h.
[0022] The second aspect of the present disclosure provides nano ZSM-5 molecular sieve aggregates prepared by the method described in the first aspect of the present disclosure.
[0023] The third aspect of the present disclosure provides a nano ZSM-5 molecular sieve aggregate, wherein the nano ZSM-5 molecular sieve aggregate comprises ZSM-5 molecular sieve grains, and the nano ZSM-5 molecular sieve aggregate is formed into a granular state; in terms of crystallinity, in the nano ZSM-5 molecular sieve aggregate, the mass fraction of the ZSM-5 molecular sieve grains is 60-95%.
[0024] Optionally, the average particle size of the nano ZSM-5 molecular sieve aggregates is 1-10 μm, and the average particle size of the ZSM-5 molecular sieve grains is 50-250 nm.
[0025] Optionally, the micropore volume of the nano ZSM-5 molecular sieve aggregate is 0.07-0.15 cm 3 / g, and the mesopore volume is 0.06-0.12cm 3 / g.
[0026] The fourth aspect of the present disclosure provides use of the nano ZSM-5 molecular sieve aggregates described in the second aspect or the third aspect of the present disclosure in a catalytic cracking reaction.
[0027] Through the above technical scheme, the present invention accurately regulates chemical processes such as silicon source dissolution, crystal nucleation, and crystal growth under hydrothermal conditions by regulating the synthesis conditions, and obtains nano ZSM-5 molecular sieve aggregates containing solid-phase silicon source and ZSM-5 molecular sieve crystallized on the surface of the solid-phase silicon source. The nano ZSM-5 molecular sieve aggregates disclosed in the present invention further reduce diffusion restrictions and improve the catalytic activity of nano ZSM-5 molecular sieve aggregates on the basis of maintaining the microporous structure of the nano molecular sieve, strengthening mass transfer diffusion, and improving the wear resistance of the molecular sieve. The method disclosed in the present invention can control the primary crystal size of the molecular sieve product to be nanometer-level, and the obtained nano ZSM-5 molecular sieve aggregates are easy to filter and recover, reducing industrial production costs. The preparation method disclosed in the present invention is simple in process, does not require multi-step synthesis, saves production costs, has higher technical and economic efficiency, and has better environmental effects.
[0028] Other features and advantages of the present disclosure will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] The accompanying drawings are used to provide a further understanding of the present disclosure and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present disclosure but do not constitute a limitation of the present disclosure. In the accompanying drawings:
[0030] Figure 1 This is the XRD diagram of the product obtained in Example 1 of the present disclosure.
[0031] Figure 2 This is a low-magnification scanning electron microscope image of the product obtained in Example 1 of the present disclosure.
[0032] Figure 3 This is a high-magnification scanning electron microscope image of the product obtained in Example 1 of the present disclosure.
[0033] Figure 4 This is the isothermal adsorption curve of the product obtained in Example 1 of the present disclosure.
[0034] Figure 5 This is the XRD diagram of the product obtained in Comparative Example 1 of the present disclosure.
[0035] Figure 6 This is a scanning electron microscope image of the product obtained in Comparative Example 1 of the present disclosure.
[0036] Figure 7 This is a scanning electron microscope image of the product obtained in Comparative Example 2 of the present disclosure.
[0037] Figure 8 This is a scanning electron microscope image of the product obtained in Comparative Example 3 of the present disclosure.
[0038] Fig. 9 This is a scanning electron microscope image of the product obtained in Comparative Example 4 of the present disclosure. DETAILED DESCRIPTION
[0039] The specific implementation of the present disclosure is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described herein is only used to illustrate and explain the present disclosure, and is not used to limit the present disclosure.
[0040] The first aspect of the present disclosure provides a method for preparing nano ZSM-5 molecular sieve aggregates, the method comprising the following steps:
[0041] (1) mixing an organosilicon source, ethanol and water for a first mixing, and then adding a template for a second mixing to obtain a seed crystal mother solution; subjecting the seed crystal mother solution to a first crystallization reaction, and separating seed crystals from the obtained material;
[0042] (2) mixing an aluminum source, an alkali source and water for a third mixing, adding an inorganic silicon source for a fourth mixing, then adding the seed crystals described in step (1) for a fifth mixing to obtain a crystallization precursor solution;
[0043] (3) subjecting the crystallization precursor solution to a second crystallization reaction and a third crystallization reaction in sequence, wherein the temperature of the second crystallization reaction is higher than the temperature of the third crystallization reaction by more than 30° C.;
[0044] Wherein, in step (2), the inorganic silicon source is one or more of diatomaceous earth, white carbon black and solid silica gel, and the average particle size of the inorganic silicon source is 0.05-25 μm; the seed crystal is 2 The mass ratio of the inorganic silicon source is 1-10:1.
[0045] The preparation method disclosed in the present invention can control the primary crystal size of the molecular sieve product to the nanometer level, and the obtained nano ZSM-5 molecular sieve aggregates are easy to filter and recover, thereby reducing industrial production costs; at the same time, the process disclosed in the present invention is simple, does not require multi-step synthesis, saves production costs, has higher technical and economic benefits, and has better environmental effects.
[0046] The present disclosure adopts a solid-phase silicon source and in-situ synthesized nano ZSM-5 molecular sieve aggregates. On the basis of maintaining the microporous structure of the nano molecular sieve, strengthening mass transfer diffusion, and improving the wear resistance of the molecular sieve, intercrystalline stacking mesopores are introduced, which further reduces the diffusion limitation and improves the catalytic activity of the molecular sieve material. The nano ZSM-5 molecular sieve aggregates obtained in the present disclosure have high conversion activity in macromolecular cracking reactions, have high macromolecular catalytic cracking activity, and have a high yield of deep cracking products. The nano ZSM-5 molecular sieve aggregates obtained in the present disclosure can achieve product separation by simple filtration. In addition, the present disclosure uses a seed crystal method, which further reduces production costs and is conducive to industrial promotion and application.
[0047] According to an embodiment of the present disclosure, in step (1), the first mixing conditions include: under stirring, the temperature is 20-35°C, and the time is 0.5-2h; the second mixing conditions include: under stirring, the temperature is 50-80°C, preferably 55-75°C, and the time is 4-8h, preferably 5-7h; in a further embodiment, the stirring rate can be 100-350rpm, preferably 150-300rpm. The above embodiment is conducive to obtaining nano ZSM-5 molecular sieve aggregates with high crystallinity and large micropore volume, which have higher macromolecular catalytic cracking activity and higher product yield when used for catalytic cracking.
[0048] According to one embodiment of the present disclosure, in step (1), SiO 2 The molar ratio of the organosilicon source, the ethanol, the template and the water is 1: (3.2-4.8): (0.16-0.24): (48-72); preferably 1: (3: 52-4.48): (0.17-0.23): (52-68). The above embodiment is conducive to obtaining nano ZSM-5 molecular sieve aggregates with high crystallinity and large micropore volume, which have higher macromolecular catalytic cracking activity and higher product yield when used for catalytic cracking.
[0049] According to an embodiment of the present disclosure, in step (1), the seed crystal is nanoscale with an average particle size of 50-300 nm; the seed crystal is pure silicon seed crystal. The above embodiment is conducive to obtaining nano molecular sieve aggregates.
[0050] According to an embodiment of the present disclosure, the conditions of the first crystallization reaction include: a temperature of 110-130°C, a time of 16-72 hours, and the first crystallization is a static crystallization. The above embodiment is conducive to obtaining nano ZSM-5 molecular sieve aggregates with high crystallinity and large micropore volume, which have higher macromolecular catalytic cracking activity and higher product yield when used for catalytic cracking.
[0051] According to one embodiment of the present disclosure, the organic silicon source is an orthosilicate, and the orthosilicate is selected from one or more of tetraethyl orthosilicate and methyl orthosilicate; the template is a quaternary ammonium compound, and the quaternary ammonium compound is selected from one or more of tetrapropylammonium hydroxide, tetramethylammonium hydroxide and tetraethylammonium hydroxide.
[0052] According to an embodiment of the present disclosure, in step (2), the third mixing conditions include: under stirring, the temperature is 20-35°C, and the time is 0.5-2h; the fourth mixing conditions include: under stirring, the temperature is 50-80°C, preferably 55-75°C, and the time is 2-4h, preferably 2.5-3.5h; the fifth mixing conditions include: under stirring, the temperature is 50-80°C, preferably 55-75°C, and the time is 1-4h, preferably 2-3h. The above-mentioned embodiment is conducive to obtaining nano ZSM-5 molecular sieve aggregates with high crystallinity and large micropore volume, which have higher macromolecular catalytic cracking activity and higher product yield when used for catalytic cracking.
[0053] According to one embodiment of the present disclosure, in step (2), SiO 2 The inorganic silicon source is Al 2 O 3 The aluminum source is calculated as Na 2 The molar ratio of the alkali source in terms of SiO2 to the water is 1:(0.012-0.018):(0.12-0.18):(25-38), preferably 1:(0.013-0.017):(0.13-0.17):(27.5-35); the seed crystal and the SiO2 2 The mass ratio of the inorganic silicon source is 3-10:1, preferably 4.4-8.6:1. The above-mentioned implementation is conducive to providing more crystal nuclei for the formation of molecular sieves, making the size of the primary crystals of the molecular sieve product smaller, and is conducive to obtaining nano ZSM-5 molecular sieve aggregates with high crystallinity and large micropore volume. When used for catalytic cracking, it has higher macromolecular catalytic cracking activity and higher product yield.
[0054] According to one embodiment of the present disclosure, step (2) further comprises adding a structural aid during the fifth mixing, wherein the structural aid is a water-soluble inorganic sodium salt, such as one or more of sodium bromide, sodium chloride, sodium nitrate and sodium carbonate, preferably sodium bromide. In a further embodiment, in the crystallization precursor solution of step (2), the structural aid and SiO 2 The molar ratio of the inorganic silicon source is 0.12-0.18:1, preferably 0.13-0.17:1. The above implementation can promote molecular sieve nucleation, shorten the crystallization time, cooperate with solid silicon source and other conditions to form nanocrystalline ZSM-5 molecular sieve, and accelerate the crystallization rate.
[0055] According to one embodiment of the present disclosure, in step (2), the aluminum source is an aluminum-containing compound selected from one or more of sodium aluminate, aluminum chloride, aluminum sulfate, aluminum isopropoxide and aluminum nitrate; the inorganic silicon source is SiO 2 The solid silicon source having a content higher than 90% by weight is selected from one or more of diatomaceous earth, white carbon black and solid silica gel; the average particle size of the inorganic silicon source is 0.05-25 μm; the alkali source is selected from one or more of sodium hydroxide and potassium hydroxide. In one embodiment, the average particle size of the inorganic silicon source can be greater than 25 microns, and the silicon source fine powder is obtained by fully grinding the silicon source raw material; the grinding is completed by a ball mill, and the present disclosure does not specifically limit the ball mill, which can be well known to those skilled in the art, such as a planetary ball mill, the ball milling time can be 1 to 5 hours, and the rotation speed can be 100 to 500 rpm. Planetary ball mills are well known to those skilled in the art, such as the JC-QM series vertical planetary ball mill of Juchuang Environmental Protection. The average particle size of the inorganic silicon source is measured by laser diffraction particle size analysis, see GB / T 19077-2016. The particle size refers to the diameter of the inorganic silicon source particles.
[0056] According to an embodiment of the present disclosure, in step (3), the conditions of the second crystallization reaction include: a temperature of 190-220°C, preferably 195-215°C, a time of 0.5-3h, preferably 1-2.5h, and the second crystallization reaction is dynamic crystallization; the conditions of the third crystallization reaction include: a temperature of 150-180°C, preferably 160-170°C, a time of 6-15h, preferably 7-13h, and the third crystallization reaction is dynamic crystallization; the temperature of the second crystallization reaction is 30-50°C higher than the temperature of the third crystallization reaction. The above embodiment is conducive to obtaining nano ZSM-5 molecular sieve aggregates with high crystallinity and large micropore volume, and when used for catalytic cracking, it has higher macromolecular catalytic cracking activity and higher product yield.
[0057] According to one embodiment of the present disclosure, the method further comprises: filtering, washing, drying and roasting the product obtained in step (3) in sequence; the roasting conditions comprise: a temperature of 500-600°C, preferably 525-575°C, and a time of 4-8h, preferably 5-7h.
[0058] The second aspect of the present disclosure provides nano ZSM-5 molecular sieve aggregates prepared by the method described in the first aspect of the present disclosure.
[0059] The third aspect of the present disclosure provides a nano ZSM-5 molecular sieve aggregate, wherein the nano ZSM-5 molecular sieve aggregate comprises ZSM-5 molecular sieve grains; the nano ZSM-5 molecular sieve aggregate is formed into a granular state; and in terms of crystallinity, in the nano ZSM-5 molecular sieve aggregate, the mass fraction of the ZSM-5 molecular sieve grains is 60-95%.
[0060] According to one embodiment of the present disclosure, the average particle size of the nano ZSM-5 molecular sieve aggregates is 1-10 μm, preferably 1-8 μm; the average particle size of the ZSM-5 molecular sieve grains is 50-250 nm, preferably 60-200 nm.
[0061] According to one embodiment of the present disclosure, the micropore volume of the nano ZSM-5 molecular sieve aggregate is 0.07-0.15 cm 3 / g, preferably 0.08 to 0.12 cm 3 / g; mesopore volume is 0.06-0.12cm 3 / g, preferably 0.08 to 0.11 cm 3 / g.
[0062] The fourth aspect of the present disclosure provides use of the nano ZSM-5 molecular sieve aggregates described in the second aspect or the third aspect of the present disclosure in a catalytic cracking reaction.
[0063] The present invention is further illustrated by the following examples, but the present invention is not limited thereto.
[0064] The tetraethyl orthosilicate (TEOS) used in the present disclosure was purchased from Inotech, product number A69114; the tetrapropylammonium hydroxide (TPAOH) used was purchased from Inotech, product number A64568. Unless otherwise specified, the other reagents were commercially available.
[0065] In the embodiments and comparative examples, the average particle size of the nano ZSM-5 molecular sieve aggregates and the ZSM-5 molecular sieve is obtained by randomly measuring the sizes of 20 ZSM-5 molecular sieves (or ZSM-5 molecular sieve aggregates) in an electron microscope (Hitachi scanning electron microscope, S-4800) image using Nano Measurer software. During the measurement process, the size of a ZSM-5 molecular sieve (or ZSM-5 molecular sieve aggregate) is the straight-line distance obtained by connecting the two farthest endpoints on the particle in the electron microscope image.
[0066] The average particle size of the nano ZSM-5 molecular sieve aggregates and the average particle size of the inorganic silicon source are equivalent volume diameters obtained by laser particle size method, and the testing instrument is Malvern Mastersizer 3000.
[0067] The relative crystallinity refers to the ASTM D3906-03 standard, and the ratio of the characteristic peak area of the crystallized product XRD spectrum at 2θ angle between 22.5-25.0° to the characteristic peak area of the standard molecular sieve is defined as the relative crystallinity. The test instrument is a D5005 X-ray diffractometer from Siemens, Germany. The test conditions are Cu target, Kα radiation, solid detector, tube voltage 40kV, tube current 40mA, step scan, step width 0.02°, prefabrication time 2s, and 2θ scanning range 5°~70°.
[0068] The pore size distribution is measured by low-temperature nitrogen adsorption capacity method, and the testing instrument is ASAP2400 static nitrogen adsorption instrument of Micromeritics Company; the testing conditions are that the sample is vacuum degassed at 1.33Pa and 300°C for 4h, and then contacted with liquid nitrogen at 77K, isothermally adsorbed and desorbed, adsorption and desorption isotherms are measured, specific surface area and pore volume are calculated using BET formula, and average pore size is calculated using BJH formula.
[0069] The ball mill adopts Juchuang environmental protection vertical planetary ball mill (JC-QM-0.4).
[0070] Example 1
[0071] The inorganic silicon source used in this embodiment is diatomite (Lingshou County Fengheng Mineral Products Processing Plant, diatomite powder, SiO 2 The mass fraction is 95%), the diatomaceous earth is fully ball-milled for 2 hours at a rotation speed of 400 rpm to obtain ground diatomaceous earth with an average particle size of 11.2 microns;
[0072] (1) TEOS (tetraethyl orthosilicate) was dissolved in ethanol (EtOH), stirred at 25° C. for 10 minutes, deionized water was added and stirred for 40 minutes, template agent TPAOH was added dropwise, and then the mixture was covered with a sealing film and stirred at 60° C. for 6 hours to obtain a seed mother solution; in this embodiment, SiO 2 Silicon source: EtOH: Template: H 2 The molar ratio of O is 1:4:0.2:60; the seed crystal mother liquor obtained above is placed in a crystallization kettle, and after crystallization in an oven at 120°C for 24 hours, centrifuged, washed with deionized water, and dried to obtain seed crystals;
[0073] (2) Weigh sodium hydroxide, sodium aluminate, and water, and stir them evenly at 25° C.; add the ground diatomaceous earth, stir at 80° C. for 3 hours, then add the seed crystals described in step (1), and continue stirring at 80° C. for 1 hour to obtain a crystallization precursor solution; in this embodiment, the crystallization precursor solution is SiO 2 Inorganic silicon source: Al 2 O 3 The aluminum source is calculated as Na 2 Alkalinity source based on H O 2 O molar ratio is 1:0.015:0.15:31.3; seed crystal: SiO 2 The mass ratio of the inorganic silicon source is 5:1;
[0074] (3) The crystallization precursor solution obtained above is charged into a crystallization kettle, and is first subjected to dynamic crystallization at 210°C for 1 hour, and then to dynamic crystallization at 170°C for 8 hours; after the crystallization reaction is completed, the crystallized mixture is filtered, washed, and dried in sequence, and the dried crystallized product is calcined at 550°C for 6 hours to obtain nano ZSM-5 molecular sieve aggregates.
[0075] The XRD spectrum of the obtained product is as follows Figure 1 As shown, it can be seen that the obtained nano ZSM-5 molecular sieve aggregate has the characteristic diffraction peak of ZSM-5 molecular sieve, and an obvious five-finger diffraction peak appears at 22.0-25.0°. As shown in Table 1, according to the crystallinity, the mass fraction of ZSM-5 molecular sieve in the nano ZSM-5 molecular sieve aggregate of Example 1 is 68.2%, and the average particle size of the nano ZSM-5 molecular sieve aggregate is 1.1 μm;
[0076] like Figure 2 As shown, the nano ZSM-5 molecular sieve aggregates exist in a particle state.
[0077] like Figure 3 As shown, the outer surface of the nano ZSM-5 molecular sieve aggregate is densely distributed with ZSM-5 molecular sieve grains, and the average particle size of the ZSM-5 molecular sieve is 150 nm (Table 1).
[0078] like Figure 4 As shown in Table 1, a hysteresis loop can be observed in the adsorption isotherm, and the presence of mesopores in the nano ZSM-5 molecular sieve aggregates in Example 1 can be observed from the pore size distribution curve. As shown in Table 1, the micropore volume of the nano ZSM-5 molecular sieve aggregates in Example 1 is 0.10 cm 3 / g, mesopore volume is 0.10cm 3 / g.
[0079] Example 2
[0080] The inorganic silicon source used in this example is white carbon black (Siedli Chemical, SiO 2 The mass fraction is 97%), and the white carbon black is fully ball-milled for 4 hours at a rotation speed of 200 rpm to obtain ground white carbon black with an average particle size of 12.0 microns;
[0081] (1) TEOS (tetraethyl orthosilicate) was dissolved in ethanol (EtOH), stirred at 25° C. for 10 minutes, deionized water was added and stirred for 40 minutes, template agent TPAOH was added dropwise, and then the mixture was covered with a sealing film and stirred at 60° C. for 6 hours to obtain a seed mother solution; in this embodiment, SiO 2 Silicon source: EtOH: Template: H 2 The molar ratio of O is 1:3.7:0.19:55.4; the seed crystal mother liquor obtained above is placed in a crystallization kettle, and after crystallization in an oven at 120°C for 24 hours, centrifuged, washed with deionized water, and dried to obtain seed crystals;
[0082] (2) Weigh sodium hydroxide, aluminum chloride, and water, and stir them evenly at 25° C.; add the ground white carbon black, stir at 80° C. for 3 hours, then add the seed crystals described in step (1), and continue stirring at 80° C. for 1 hour to obtain a crystallization precursor solution; in the crystallization precursor solution of this embodiment, SiO 2 Silicon source: Al 2 O 3 The aluminum source is calculated as Na 2 Alkalinity source based on H O 2 O molar ratio is 1:0.014:0.14:28.9; seed: SiO 2 The mass ratio of the inorganic silicon source is 4.6:1;
[0083] (3) The crystallization precursor solution obtained above is charged into a crystallization kettle, and dynamic crystallization is first performed at 210°C for 1 hour, and then at 170°C for 8 hours; after the crystallization reaction is completed, the crystallized mixture is filtered, washed, and dried in sequence, and the dried crystallized product is calcined at 550°C for 6 hours to obtain nano ZSM-5 molecular sieve aggregates.
[0084] As shown in Table 1, according to the crystallinity, the mass fraction of ZSM-5 molecular sieve in the nano ZSM-5 molecular sieve aggregate of Example 2 is 83.5%, and the average particle size of the nano ZSM-5 molecular sieve aggregate particles is 2.8 μm; ZSM-5 molecular sieve grains are densely distributed on the outer surface of the nano ZSM-5 molecular sieve aggregate, and the average particle size of the ZSM-5 molecular sieve is 180 nm (Table 1); a hysteresis loop can be observed in the adsorption isotherm, and the presence of mesopores in the nano ZSM-5 molecular sieve aggregate can be observed from the pore size distribution curve. As shown in Table 2, the micropore volume of the nano ZSM-5 molecular sieve aggregate in Example 2 is 0.12 cm 3 / g, and the mesopore volume is 0.09cm 3 / g.
[0085] Example 3
[0086] The inorganic silicon source used in this example is solid silica gel (Qingdao Jiyida Silica Gel Reagent Co., Ltd., SiO 2 The mass fraction is 99%) and the ball milling is performed (ball milling time is 5 hours, rotation speed is 400 rpm) to obtain silicon source fine powder with an average particle size of 18.1 microns;
[0087] (1) TEOS (tetraethyl orthosilicate) was dissolved in ethanol (EtOH), stirred at 25° C. for 10 minutes, deionized water was added and stirred for 40 minutes, template agent TPAOH was added dropwise, and then the mixture was covered with a sealing film and stirred at 60° C. for 6 hours to obtain a seed mother solution; in this embodiment, SiO 2 Silicon source: EtOH: Template: H 2 The molar ratio of O is 1:4.3:0.2:63.8; the seed crystal mother liquor obtained above is placed in a crystallization kettle, and after crystallization in an oven at 120 degrees for 24 hours, centrifuged, washed with deionized water, and dried to obtain seed crystals;
[0088] (2) Weigh sodium hydroxide, aluminum sulfate, and water, and stir them evenly at 25° C.; add the ground solid silica gel, stir at 80° C. for 3 hours, then add the seed crystals described in step (1), and continue stirring at 80° C. for 1 hour to obtain a crystallization precursor solution; in the crystallization precursor solution of this embodiment, SiO 2 Inorganic silicon source: Al 2 O 3 The aluminum source is calculated as Na 2 Alkalinity source based on H O 2 O molar ratio is 1:0.016:0.160:33.3; seed crystal: SiO 2 The mass ratio of the inorganic silicon source is 8.2:1;
[0089] (3) The crystallization precursor solution obtained above is charged into a crystallization kettle, and is first subjected to dynamic crystallization at 210°C for 1 hour, and then to dynamic crystallization at 170°C for 8 hours; after the crystallization reaction is completed, the crystallized mixture is filtered, washed, and dried in sequence, and the dried crystallized product is calcined at 550°C for 6 hours to obtain nano ZSM-5 molecular sieve aggregates.
[0090] As shown in Table 1, according to the crystallinity, the mass fraction of ZSM-5 molecular sieve in the nano ZSM-5 molecular sieve aggregate of Example 3 is 91.2%, and the average particle size of the nano ZSM-5 molecular sieve aggregate particles is 4.5 μm; the outer surface of the nano ZSM-5 molecular sieve aggregate is densely distributed with ZSM-5 molecular sieve grains, and the average particle size of the ZSM-5 molecular sieve is 115 nm (Table 1); a hysteresis loop can be observed in the adsorption isotherm, and the presence of mesopores in the nano ZSM-5 molecular sieve aggregate can be observed from the pore size distribution curve, and the micropore volume of the nano ZSM-5 molecular sieve aggregate of Example 3 is 0.14 cm 3 / g, and the mesopore volume is 0.08cm 3 / g.
[0091] Example 4
[0092] The method of this embodiment is the same as that of embodiment 1, except that the seed mother solution is changed in step (1) to SiO 2 Silicon source: EtOH: Template: H 2 The molar ratio of O is 1:3.3:0.16:49.3; in step (2), the crystallization precursor solution is SiO 2 Inorganic silicon source: Al 2 O 3 The aluminum source is calculated as Na 2 Alkalinity source based on H O 2 The molar ratio of O is 1:0.012:0.12:25.6; seed: SiO 2 SiO 2 The mass ratio of the inorganic silicon source is 4.1:1.
[0093] As shown in Table 1, according to the crystallinity, the mass fraction of ZSM-5 molecular sieve in the nano ZSM-5 molecular sieve aggregate in Example 4 is 62.2%; the nano ZSM-5 molecular sieve aggregate exists in a particle state, and the average particle size of the nano ZSM-5 molecular sieve aggregate is 7.2 μm; the outer surface of the nano ZSM-5 molecular sieve aggregate is densely distributed with ZSM-5 molecular sieve particles, and the average particle size of the ZSM-5 molecular sieve is 65 nm (Table 1); a hysteresis loop can be observed in the adsorption isotherm, and it can be observed from the pore size distribution curve that there are mesopores in the nano ZSM-5 molecular sieve aggregate, and the micropore volume of the nano ZSM-5 molecular sieve aggregate in Example 4 is 0.08 cm 3 / g, and the mesopore volume is 0.11cm 3 / g.
[0094] Example 5
[0095] The method of this embodiment is the same as that of embodiment 1, except that in step (1), SiO 2 Silicon source: EtOH: Template: H 2 The molar ratio of O is 1:4.7:0.24:70.8; in step (2), the crystallization precursor solution is SiO 2 Inorganic silicon source: Al 2 O 3 The aluminum source is calculated as Na 2 Alkalinity source based on H O 2 O molar ratio is 1:0.018:0.18:36.9; seed: SiO 2 The mass ratio of the inorganic silicon source is 8.9:1.
[0096] As shown in Table 1, according to the crystallinity, the mass fraction of ZSM-5 molecular sieve in the nano ZSM-5 molecular sieve aggregate of Example 5 is 68.4%; the nano ZSM-5 molecular sieve aggregate exists in a particle state, and the average particle size of the nano ZSM-5 molecular sieve aggregate is 9.1 μm; the outer surface of the nano ZSM-5 molecular sieve aggregate is densely distributed with ZSM-5 molecular sieve particles, and the average particle size of the ZSM-5 molecular sieve is 240 nm (Table 1); a hysteresis loop can be observed in the adsorption isotherm, and it can be observed from the pore size distribution curve that there are mesopores in the nano ZSM-5 molecular sieve aggregate, and the micropore volume of the nano ZSM-5 molecular sieve aggregate in Example 5 is 0.09 cm 3 / g, and the mesopore volume is 0.11cm 3 / g.
[0097] Example 6
[0098] The method of this embodiment is the same as that of embodiment 1, except that in step (1), SiO 2 Silicon source: EtOH: Template: H 2 The molar ratio of O is 1:2.2:0.15:80; in step (2), the crystallization precursor solution is SiO 2 Inorganic silicon source: Al 2 O 3 The aluminum source is calculated as Na 2 Alkalinity source based on H O 2 O molar ratio is 1:0.010:0.10:40; seed crystal: SiO 2 The mass ratio of the inorganic silicon source is 2:1.
[0099] As shown in Table 1, according to the crystallinity, the mass fraction of ZSM-5 molecular sieve in the nano ZSM-5 molecular sieve aggregates of Example 6 is 67.1%; the nano ZSM-5 molecular sieve aggregates exist in a particle state, and the average particle size of the nano ZSM-5 molecular sieve aggregates is 8.3 μm; the outer surface of the nano ZSM-5 molecular sieve aggregates is densely distributed with ZSM-5 molecular sieve particles, and the average particle size of the ZSM-5 molecular sieve is 220 nm (Table 1); a hysteresis loop can be observed in the adsorption isotherm, and it can be observed from the pore size distribution curve that there are mesopores in the nano ZSM-5 molecular sieve aggregates, and the micropore volume of the nano ZSM-5 molecular sieve aggregates in Example 6 is 0.08 cm 3 / g, and the mesopore volume is 0.09cm 3 / g.
[0100] Example 7
[0101] The method of this embodiment is the same as that of embodiment 1, except that in step (3), the temperature of the second crystallization reaction is 170° C., and the temperature of the third crystallization reaction is 140° C.
[0102] As shown in Table 1, according to the crystallinity, the mass fraction of ZSM-5 molecular sieve in the nano ZSM-5 molecular sieve aggregate of Example 7 is 60.2%; the nano ZSM-5 molecular sieve aggregate exists in a particle state, and the average particle size of the nano ZSM-5 molecular sieve aggregate is 9.5 μm; ZSM-5 molecular sieve particles are loosely distributed on the outer surface of the nano ZSM-5 molecular sieve aggregate, and the average particle size of the ZSM-5 molecular sieve is 250 nm (Table 1); the micropore volume of the nano ZSM-5 molecular sieve aggregate in Example 7 is 0.08 cm 3 / g, and the mesopore volume is 0.08cm 3 / g.
[0103] Comparative Example 1
[0104] The preparation method of this comparative example does not include the process of preparing seed crystal mother solution and seed crystal; the inorganic silicon source used in this comparative example is diatomaceous earth (Lingshou County Fengheng Mineral Products Processing Plant, diatomaceous earth powder, SiO 2 The mass fraction is 95%), the diatomaceous earth is fully ball-milled for 2 hours at a rotation speed of 400 rpm to obtain ground diatomaceous earth with an average particle size of 11.2 microns;
[0105] Weigh sodium hydroxide, sodium aluminate, and water, and stir them evenly at 25°C; add ground diatomaceous earth, and stir at 80°C for 3 hours to obtain a crystallization precursor solution; in the crystallization precursor solution, SiO 2 Inorganic silicon source: Al 2 O 3 The aluminum source is calculated as Na 2 Alkalinity source based on H O 2The molar ratio of O is 1:0.015:0.15:31.3;
[0106] The crystallization precursor solution obtained above was charged into a crystallization kettle, and was first subjected to dynamic crystallization at 210°C for 1 hour, and then to dynamic crystallization at 170°C for 8 hours. After the crystallization reaction was completed, the crystallized mixture was filtered, washed, and dried in sequence, and the dried crystallized product was calcined at 550°C for 6 hours to obtain the product.
[0107] The XRD spectrum of the product is as follows Figure 5 As shown, it can be seen that although the obtained product has the characteristic diffraction peaks of ZSM-5 molecular sieve, and 2θ shows a five-finger diffraction peak at 22.0-25.0°, a strong diffraction peak of heterocrystalline mordenite MOR is also observed in the XRD spectrum. As shown in Table 1, according to the crystallinity, the mass fraction of ZSM-5 molecular sieve in the nano ZSM-5 molecular sieve of Comparative Example 1 is only 21%.
[0108] The SEM image of the product of this comparative example 1 is as follows Figure 6 As shown, it can be seen that no nano ZSM-5 molecular sieve aggregates were observed in the product obtained in Comparative Example 1, and only micron-sized mordenite impurities and ZSM-5 molecular sieves dispersed and attached to the outer surface of the impurities were observed.
[0109] Comparative Example 2
[0110] The method of this comparative example is the same as that of Example 1, except that a commercial molecular sieve (Nankai H-type ZSM-5 molecular sieve, silicon-aluminum molecular molar ratio 38, crystallinity 85.5%, size 9.517×4.039 μm) is used as the seed crystal.
[0111] As shown in Table 1, Figure 7 As shown, no nano ZSM-5 molecular sieve aggregates were observed, and the product obtained in Comparative Example 2 was a mixture of MOR molecular sieve and ZSM-5 molecular sieve, with a mass fraction of ZSM-5 molecular sieve of 32% (based on crystallinity).
[0112] Comparative Example 3
[0113] The preparation method of this comparative example is the same as that of Example 1, except that in step (3), one-stage low-temperature dynamic crystallization is adopted, and the crystallization condition is low-temperature crystallization at 170° C. for 9 hours.
[0114] As shown in Table 1 and Figure 8 As shown, the product obtained in Comparative Example 3 is a mixture of MOR molecular sieve and ZSM-5 molecular sieve, and the mass fraction of ZSM-5 molecular sieve is 14% (based on crystallinity).
[0115] Comparative Example 4
[0116] The preparation method of this comparative example is the same as that of Example 1, except that in step (3), a one-stage high-temperature dynamic crystallization is adopted, and the crystallization condition is a high-temperature crystallization at 210° C. for 9 hours.
[0117] As shown in Table 1 and Fig. 9 As shown, no ZSM-5 molecular sieve was observed in the product obtained in Comparative Example 4, and only a mixture of MOR molecular sieve and quartz was observed.
[0118] Comparative Example 5
[0119] The preparation method of this comparative example is the same as that of Example 1, except that in step (3), the crystallization is first performed at low temperature and then at high temperature, the second crystallization reaction temperature is 170°C, and the third crystallization reaction temperature is 210°C.
[0120] As shown in Table 1, the product obtained in Comparative Example 5 is a mixture of mordenite MOR molecular sieve and ZSM-5 molecular sieve, and the crystallinity of the ZSM-5 molecular sieve is 15%.
[0121] Comparative Example 6
[0122] The method of this comparative example is the same as that of Example 1, except that in step (2), the ground diatomaceous earth and the seed crystals described in step (1) are added simultaneously, and the mixture is stirred at 80° C. for 4 h.
[0123] As shown in Table 1, the product obtained in Comparative Example 6 is a mixture of mordenite MOR molecular sieve and ZSM-5 molecular sieve, and the crystallinity of the ZSM-5 molecular sieve is 11%.
[0124] Test Example 1
[0125] The products prepared in Examples 1-7 and Comparative Examples 1-6 were subjected to XRD, SEM and low temperature nitrogen adsorption tests. The results are shown in Tables 1 and Figure 1-9 .
[0126] Table 1
[0127]
[0128] According to the data in Table 1, compared with the comparative example, the nano ZSM-5 molecular sieve aggregates obtained by the method disclosed in the present invention have an initial grain size of nanometer scale and high crystallinity, a large micropore volume and a mesoporous structure, and are multi-level porous materials.
[0129] Test Example 2
[0130] The products prepared in Examples 1-7 and Comparative Examples 1-6 were used for catalytic cracking, and the specific method was as follows:
[0131] The nano ZSM-5 molecular sieve aggregate powder obtained in Example 1 was placed in an aqueous ammonium sulfate solution with a concentration of 0.1 g / mL (powder: ammonium sulfate mass ratio = 1:1), and stirred at 80°C for 2 hours for ion exchange, and exchanged twice in total to obtain ammonia-type nano ZSM-5 molecular sieve aggregate powder; then the nano ZSM-5 molecular sieve aggregate powder was washed with water, dried, and calcined at 550°C for 4 hours to obtain hydrogen-type nano ZSM-5 molecular sieve aggregate powder; the hydrogen-type nano ZSM-5 molecular sieve aggregate powder was tableted and sieved to obtain 40-60 mesh catalyst particles for catalytic cracking experiments.
[0132] The catalyst particles were placed in a fixed bed reactor, the reaction pressure was 0.1 MPa, the reaction temperature was 500 °C, and the feed weight hourly space velocity (WHSV) of the raw material (1,3,5 triisopropylbenzene, abbreviated as TIPB) was 80 h -1 ; The agent-oil ratio is 0.6:1 (weight ratio). After the reaction, the liquid phase material is collected by cooling, and the gas phase product is collected by drainage gas collection method. The liquid phase product is analyzed by Agilent 7890B (HP-PONA column) chromatography, and the gas phase product is analyzed by Agilent 6890 chromatography. The results are shown in Table 2.
[0133] The tests of Examples 2-7 and Comparative Examples 1-6 were the same as those of Example 1 above.
[0134] The TIPB conversion rate is calculated according to the following formula: conversion rate = 1-(mass of TIPB in liquid product / mass of TIPB raw material); benzene selectivity = mass of benzene in product ÷ (mass of TIPB raw material × conversion rate).
[0135] Table 2
[0136]
[0137]
[0138] As shown in Table 2, when the molecular sieve product obtained by the method of the present invention is subjected to catalytic cracking reaction, the conversion rate is significantly higher than that of the comparative example under the same reaction conditions, and the benzene selectivity in the deep cracking product is significantly higher than that of the comparative example, showing a good catalytic effect. By comparing Example 1 with Example 6, it can be seen that within the preferred ratio range of the seed mother solution and the crystallization precursor solution of the present invention, and within the mass ratio range of the seed and the inorganic silicon source, when the nano ZSM-5 molecular sieve aggregate is obtained for catalytic cracking reaction, the conversion rate is higher, and the benzene selectivity in the deep cracking product is also higher. By comparing Example 1 with Example 7, it can be seen that within the condition range of the second crystallization reaction and the third crystallization reaction of the present invention, when the nano ZSM-5 molecular sieve aggregate is obtained for catalytic cracking reaction, the conversion rate is higher, and the benzene selectivity in the deep cracking product is also higher.
[0139] The preferred embodiments of the present disclosure are described in detail above in conjunction with the accompanying drawings; however, the present disclosure is not limited to the specific details in the above embodiments. Within the technical concept of the present disclosure, a variety of simple modifications can be made to the technical solution of the present disclosure, and these simple modifications all fall within the protection scope of the present disclosure.
[0140] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present disclosure will not further describe various possible combinations.
[0141] In addition, various embodiments of the present disclosure may be arbitrarily combined, and as long as they do not violate the concept of the present disclosure, they should also be regarded as the contents disclosed by the present disclosure.
Claims
1. A method for preparing nano ZSM-5 molecular sieve aggregates, characterized in that: The method comprises the following steps: (1) mixing an organosilicon source, ethanol and water for a first mixing, and then adding a template for a second mixing to obtain a seed crystal mother solution; subjecting the seed crystal mother solution to a first crystallization reaction, and separating seed crystals from the obtained material; (2) mixing an aluminum source, an alkali source and water for a third mixing, adding an inorganic silicon source for a fourth mixing, then adding the seed crystals described in step (1) for a fifth mixing to obtain a crystallization precursor solution; (3) subjecting the crystallization precursor solution to a second crystallization reaction and a third crystallization reaction in sequence, wherein the temperature of the second crystallization reaction is higher than the temperature of the third crystallization reaction by more than 30° C.; Wherein, in step (2), the inorganic silicon source is one or more of diatomaceous earth, white carbon black and solid silica gel, and the average particle size of the inorganic silicon source is 0.05-25 μm; the mass ratio of the seed crystal to the inorganic silicon source calculated as SiO2 is 1-10:
1.
2. The method according to claim 1, wherein: In step (1), the first mixing conditions include: stirring at a temperature of 20-35° C. for 0.5-2 h; the second mixing conditions include: stirring at a temperature of 50-80° C. for 4-8 h; In step (1), the molar ratio of the organosilicon source, the ethanol, the template and the water calculated as SiO2 is 1:(3.2-4.8):(0.16-0.24):(48-72); The conditions of the first crystallization reaction include: a temperature of 110-130°C, a time of 16-72 hours, and the first crystallization is static crystallization; The organic silicon source is orthosilicate, and the orthosilicate is selected from one or more of tetraethyl orthosilicate and methyl orthosilicate; The template agent is a quaternary ammonium compound, and the quaternary ammonium compound is selected from one or more of tetrapropylammonium hydroxide, tetramethylammonium hydroxide and tetraethylammonium hydroxide.
3. The method according to claim 1, wherein: In step (2), the third mixing conditions include: stirring at a temperature of 20-35°C for 0.5-2h; the fourth mixing conditions include: stirring at a temperature of 50-80°C for 2-4h; the fifth mixing conditions include: stirring at a temperature of 50-80°C for 1-4h.
4. The method according to claim 1, wherein: In step (2), the molar ratio of the inorganic silicon source calculated as SiO2, the aluminum source calculated as Al2O3, the alkali source calculated as Na2O and the water is 1:(0.012-0.018):(0.12-0.18):(25-38); the mass ratio of the seed crystal to the inorganic silicon source calculated as SiO2 is 3-10:
1.
5. The method according to claim 1, wherein: In step (2), the aluminum source is an aluminum-containing compound selected from one or more of sodium aluminate, aluminum trichloride, aluminum sulfate, aluminum isopropoxide and aluminum nitrate; the inorganic silicon source is a solid silicon source with a SiO2 content higher than 90 weight %; and the alkali source is selected from one or more of sodium hydroxide and potassium hydroxide.
6. The method according to claim 1, wherein: Step (2) also includes adding a structural aid during the fifth mixing; the structural aid is a water-soluble inorganic sodium salt selected from one or more of sodium bromide, sodium chloride, sodium nitrate and sodium carbonate; the molar ratio of the structural aid to the inorganic silicon source calculated as SiO2 is 0.12-0.18:1, preferably 0.13-0.17:
1.
7. The method according to claim 1, wherein: In step (3), the conditions of the second crystallization reaction include: temperature of 190-220oC, time of 0.5-3h, and the second crystallization reaction is dynamic crystallization; the conditions of the third crystallization reaction include: temperature of 150-180oC, time of 6-15h, and the third crystallization reaction is dynamic crystallization; the temperature of the second crystallization reaction is 30-50°C higher than the temperature of the third crystallization reaction.
8. The method according to claim 1, wherein: The method further comprises: filtering, washing, drying and roasting the product obtained in step (3) in sequence; the roasting conditions include: temperature of 500-600° C. and time of 4-8 hours.
9. Nano ZSM-5 molecular sieve aggregates prepared by the method according to any one of claims 1 to 8.
10. A nano ZSM-5 molecular sieve aggregate, characterized in that: The nano ZSM-5 molecular sieve aggregate comprises ZSM-5 molecular sieve crystals, and the nano ZSM-5 molecular sieve aggregate is formed into particles; according to the crystallinity, in the nano ZSM-5 molecular sieve aggregate, the mass fraction of the ZSM-5 molecular sieve crystals is 60-95%.
11. The nano ZSM-5 molecular sieve aggregate according to claim 10, wherein: The average particle size of the nano ZSM-5 molecular sieve aggregates is 1-10 μm, and the average particle size of the ZSM-5 molecular sieve grains is 50-250 nm.
12. The nano ZSM-5 molecular sieve aggregate according to claim 10, wherein: The micropore volume of the nano ZSM-5 molecular sieve aggregate is 0.07-0.15 cm 3 / g, and the mesopore volume is 0.06-0.12cm 3 / g.
13. Use of the nano ZSM-5 molecular sieve aggregates according to any one of claims 9 to 12 in catalytic cracking reactions.
Citation Information
Patent Citations
Molecular sieve aggregate and its preparation method
CN102872909A
Hydrophobic silicon zeolite adsorbent without cohesive agent and its preparation
CN1105906A